Learning between couple: the union of two worlds, visual and touch (Revista Electrónica Diálogos Educativos. REDE, 2017)
We present an experience of teacher training in Differential Education, specialization Problems of Vision, in which skills are developed in the handling of manipulative skills for the use of the Braille System through peer learning, where blind students have a leading role.Peer-to-peer learning allows a mediation that recognizes and values the relationship between students. In this case, the relationship between blind students and sighted students is a strategy for the acquisition of tactile abilities and abilities.During the workshops, the tactile learning strategies make sense in this dynamic of interaction. Only in the one-to-one interaction is it possible for the student seer to put himself in the place of his blind partner.